Causal Factors and Symptoms of Task-Related Human Fatigue in Vessel Traffic Service: A Task-Driven Approach. (23rd November 2020) - Li, Fan; Chen, Chun-Hsien; Xu, Gangyan; Chang, Danni; Khoo, Li Pheng
Abstract : Human fatigue is a major risk factor in transportation that contributes, directly or indirectly, to a large number of traffic accidents. Though many studies have investigated fatigue-inducing factors in transportation to manage human fatigue more efficiently, there are limited studies related to vessel traffic service (VTS). To fill this gap, this work aims to determine the key causal factors and symptoms of human fatigue with a focus on VTS operations. Achieving this aim is hindered by the problems of no standard definition of task-related fatigue and limited data sources. To solve these problems, this paper proposes a novel definition of task-related human fatigue, a task-driven approach for identifying causal factors and a causal network-based approach for selecting key causal factors. Twelve key causal factors of human fatigue in VTS were identified and analysed. In addition, it was found that VTS operators suffered from multidimensional fatigue, especially physical fatigue. The results provide a foundation and future directions for designing interventions to manage human fatigue.